Life Cycle Activity Analysis: an integrated environmental and economic mathematical programming decision-support model - Freire F.; Thore S. (Comprehensive economic and spatial bio-energy modelling, 2002)
Life Cycle Activity Analysis (LCAA) - a mathematical programming decision support model for the optimization of the entire life cycle of products - is presented. LCAA is a new tool for the mapping of hierarchical production and recovery chains, their impact on the environment, and for a holistic evaluation of new technologies, environmental strategies or policies. LCAA involves three successive stages of analysis: i) a description of ail participating activities (processing, transport, use, recovery, ...) as a good travels from its cradle to its grave, including the inventory of ancillary materials and energy supplied to each activity, economic costs and environmental burdens; ii) the formulation and numerical solution of a linear or nonlinear mathematical programming model and iii) the evaluation of a set of environmental scenarios of interest to policy- decision-makers or stake-holders. It is shown how LCAA contributes to the conceptualization of Industrial Ecology, which can be seen as a new paradigm for the integration of environmental and economic performance. The antecedents of LCAA (classical Activity Analysis adjoined to the environmental Life Cycle Assessment framework) are surveyed. Illustrative conceptual mathematical programming formats are discussed and the potential of LCAA, the type of problems to be addressed and its relevance to environmental policy are further explored.
Seminar on Comprehensive Economic and Spatial Bio-Energy Modelling, 2001/06/07-08, Grignon (France)